A Resolution of Reported Discrepancies in the Characteristics of Platelet Glycoproteins IV (GPIV) and III b (GPIII b) - Yamamoto, Naomasa; Romeuf, Christophe de; Tandon, Narendra N; Jamieson, G A (Thrombosis and Haemostasis, 1990)
The terms glycoprotein IV (GPIV) and glycoprotein IIIb (GPIIIb) have been used interchangeably and reports in the literature have indicated this glycoprotein as having a molecular weight variously described as either 88,000 or 97,000, a fast anodal mobility on crossed electrophoresis and either 13 or <1 methionine residues on amino acid analysis of the purified glycoprotein. To resolve these discrepancies, we have evaluated the characteristics of GPIV both in whole platelets and after isolation. These studies have shown that the term GPIV defines a protease-resistant platelet surface glycoprotein with Mr 88,330 ± 2,240 which is immunologically identical with the CD36 differentiation antigen, which migrates with a relatively slow anodal mobility on crossed immunoelectrophoresis and which contains ∼13 methionine residues per mole.
Keywords: Glycoprotein IV; Glycoprotein IIIb; Structure